Uncertain Sexualities and the Unusual Woman: Depictions of Jane Addams and Emily Dickinson. (17th January 2020) - Bartram, Robin; Brown-Saracino, Japonica; Donovan, Holly
Abstract: How does contemporary society deal with uncertainty about sexualities in the past? We investigate how two museums manage uncertainty about the sexual histories of two female biographical subjects. Contributing to understandings of how cultural institutions handle such uncertainty, and, in particular, how museums depict gender and sexualities, our paper brings together current debates in literatures on queer histories, collective memory, and sexualities and gender. Our observations at the Jane Addams Hull House Museum and the Emily Dickinson Museum reveal that both museums handle uncertainty about their subject's sexuality by conflating ambiguous sexuality with non-normative gender performance. This conflation results in the depiction of the character of the "unusual woman." While one museum relies on the "unusual woman" to evade discussions of non-normativity, the other uses the same device to acknowledge and politicize uncertainty. Our research thus reveals institutional depictions of the "unusual woman" even in an era in which many cultural institutions work to frame sexual minorities as "normal" or the "same." At the same time, our work intervenes in gender and sexualities scholarship by demonstrating that unusualness can be either obfuscatory or provocative; conflations of gender and sexuality are multifaceted and can either reproduce or disrupt normativity.